2013
DOI: 10.1007/s11926-013-0345-z
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Challenges in Spondyloarthritis Imaging for Diagnosis and Assessment of Disease

Abstract: In recent years there has been an increased focus on use of imaging for diagnosis and assessment of spondyloarthritis (SpA). Magnetic resonance imaging (MRI) has attracted particular interest for its potential to improve diagnostic certainty for early, non-radiographic disease and to assist clinical decision-making. This report summarizes recent developments toward definition of positive sacroiliac joint and spine MRIs for SpA, with erosion as the major determinant for disease classification. The report also h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…In the same way, fatty deposition at several vertebral corners orientated towards the diagnosis of axial SpA, again in younger adults [26,27]. Altogether, the different studies evaluating SIJ MRI in SpA yielded a sensitivity of between 60 and 90 % and a specificity between 70 and 95 % for the diagnosis of axial SpA [7] while spine MRI performed less well: sensitivity ranged from 30 to 60 % and specificity from 60 to 90 % [26,27]. It is noteworthy that the clinical utility of MRI for the assessment of SIJ inflammation was evaluated in young patients with AS, inflammatory back pain of recent onset, and mechanical back pain, and healthy controls, with the subjects studied generally aged under 45 years.…”
Section: Assessment Of Spondyloarthritis International Society (Asas)mentioning
confidence: 79%
See 2 more Smart Citations
“…In the same way, fatty deposition at several vertebral corners orientated towards the diagnosis of axial SpA, again in younger adults [26,27]. Altogether, the different studies evaluating SIJ MRI in SpA yielded a sensitivity of between 60 and 90 % and a specificity between 70 and 95 % for the diagnosis of axial SpA [7] while spine MRI performed less well: sensitivity ranged from 30 to 60 % and specificity from 60 to 90 % [26,27]. It is noteworthy that the clinical utility of MRI for the assessment of SIJ inflammation was evaluated in young patients with AS, inflammatory back pain of recent onset, and mechanical back pain, and healthy controls, with the subjects studied generally aged under 45 years.…”
Section: Assessment Of Spondyloarthritis International Society (Asas)mentioning
confidence: 79%
“…In addition, the modified New York criteria do not take into account the full clinical spectrum of SpA. MRI has emerged as an important imaging tool for the early detection of acute inflammation of the SIJ and/or the spine in patients with SpA [7]. In addition, it has been suggested that patients presenting with chronic inflammatory back pain before the age of 45 years are considered to have axial SpA, regardless of whether radiographic sacroiliitis is present or absent.…”
Section: Assessment Of Spondyloarthritis International Society (Asas)mentioning
confidence: 99%
See 1 more Smart Citation
“…4 and 5). 9,34,35 BME is not pathognomonic for axSpA and may occur in healthy persons and in patients with non-SpA-related back pain 36,37 (Tip 8). -Enthesitis: Inflammation at the attachment of tendons and ligaments to bone is defined as increased signal in bone marrow and/or soft tissue on fluid-sensitive sequences at sites where ligaments and tendons attach to bone.…”
Section: Acute Inflammatory Lesionsmentioning
confidence: 99%
“…As conventional radiography is considered superior to MRI in the evaluation of spinal syndesmophytes [3], follow-up of patients with axial involvement is recommended to be performed once every 2 years [4]. Thus, over their lifetime, SpA patients are repeatedly exposed to X-rays with an increased lifetime ionizing radiation exposure.…”
Section: Conventional Radiographymentioning
confidence: 99%